Aluminum- and Vanadium-free Titanium Alloys for Medical Applications - Haase Fabian; Siemers Carsten; Klinge Lina; Lu Cheng; Lang Patric; Lederer Stephan; König Till; Rösler Joachim (MATEC Web of Conferences, 2020)
CP-Ti, Ti 6A l 4V (ELI), and Ti 6Al 7Nb are often used for manufacturing osteosynthesis products or implants. However, researches have revealed that Al and V can have detrimental effects on the human body. Therefore, several Al- and V-free near-α and (α+β) titanium alloys have been developed on the basis of CP-Ti Grade 4+ (Ti 0.4O 0.5Fe 0.08C). They should possess similar or better mechanical properties than Ti 6Al 4V (ELI) combined with an improved biocompatibility and good corrosion resistance. O, C, Fe, Au, Si, Nb, or Mo have been used as alloying elements, which are either already present in the human body or are biocompatible. Several of the studied alloys show a strength and ductility fulfilling the requirements of Ti 6Al 4V ELI as specified in ASTM F136. For instance, Ti 0.44O 0.5Fe 0.08C 2.0Mo exhibits a YTS of approx. 1005 MPa, an UTS of approx. 1015 MPa, and an elongation at rupture of at least 17%. Therefore, one or more of the studied alloys are promising candidates for replacing Ti 6Al 4V ELI in osteosynthesis and implant applications.